Terapi Komplementer untuk Mengurangi Mual Muntah pada Pasien Kanker Payudara - Purba, Venbora; Waluyo, Agung; Allenidekania, Allenidekania; Gayatri, Dewi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Nausea and vomiting due to chemotherapy are still the most common side effects, causing low compliance to treatment, impaired functional activities, increased stress and depression, and decreased quality of life. Complementary therapies are expected to improve health and quality of life and can overcome nausea and vomiting in patients with breast cancer. The purpose of this review was to find and discuss complementary therapies that can reduce nausea and vomiting in patients with breast cancer. This study was a systematic review sourced from several databases, namely Medline, Embasse, ScienceDirect, ProQuest, using the keywords “complementary therapies” AND “breast cancer OR breast neoplasm OR breast carcinoma OR breast tumor” AND “nausea and vomiting”. This study found 11 articles related to complementary therapies to reduce nausea and vomiting in patients with breast cancer. From these articles, there were seven types of complementary therapies that can be used as complementary therapies to overcome nausea and vomiting, namely auricular acupressure, breathing exercise, peppermint oil, foot massage, ginger root powder, structured yoga therapy and abdomen massage. It was concluded that aromatherapy with peppermint essential oil is the most widely used complementary therapy to overcome nausea and vomiting in breast cancer patients.Keywords: breast cancer; nausea; vomiting; complementary therapy ABSTRAK Mual dan muntah akibat kemoterapi masih merupakan efek samping yang paling umum, yang menyebabkan rendahnya kepatuhan untuk pengobatan, gangguan aktivitas fungsional, peningkatan tekanan dan depresi, serta penurunan kualitas hidup. Terapi komplementer diharapkan dapat meningkatkan kesehatan dan kualitas hidup serta dapat mengatasi mual dan muntah pada pasien dengan kanker payudara. Tujuan dari tinjauan ini adalah untuk mencari dan membahas terapi komplementer yang dapat mengurangi mual dan muntah pada pasien dengan kanker payudara. Studi ini merupakan systematic review yang bersumber dari beberapa database yaitu Medline, Embasse, ScienceDirect, ProQuest, dengan menggunakan kata kunci “complementary therapies” AND “breast cancer OR breast neoplasm OR breast carcinoma OR breast tumor” AND “nausea and vomiting”. Studi ini menemukan 11 artikel terkait terapi komplementer untuk mengurangi mual muntah pada pasien dengan kanker payudara. Dari artikel-artikel tersebut ada tujuh jenis terapi komplementer yang dapat yang dapat digunakan sebagai terapi pendamping untuk mengatasi mual dan muntah, yaitu auricular acupressure, breathing exercise, peppermint oil, foot massage, ginger root powder, structured yoga therapy dan abdomen massage. Disimpulkan bahwa aromaterapi dengan minyak atsiri peppermint merupakan terapi komplementer yang paling banyak digunakan untuk mengatasi mual muntah pada pasien kanker payudara.Kata kunci: kanker payudara; mual; muntah; terapi komplementer